Why becoming a national treasure matters: Elite celebrity status and inequality in the United Kingdom. (February 2020) - Greer, Chris; McLaughlin, Eugene
This article presents the first academic analysis of 'national treasure' as a status designation for an elite category of British celebrities who hold a unique position in the Great British hall of fame. The emergence of this status designation is situated in the context of two intersecting processes of cultural change in the post-War period – the rise of celebrity culture and the popularisation of the state honours system. It is proposed that national treasure status results from the accumulation of three interlocking forms of validation: peer, state and media. After reviewing these underpinning forms of validation, we consider one of Britain's most celebrated national treasures – Dame Judi Dench. The aim is to illustrate empirically the status elevation and sedimentation processes through which particular elite celebrities become national treasures, and the various ways in which they might respond to this status designation. Although the term 'national treasure' for many – including those so-designated – may seem a trite term of endearment, we argue that it is in fact an ideological assemblage invested with significance. On one hand, national treasures help revalidate the notion of the authentic celebrity within an apparently meritocratic system that recognises and rewards talent, hard work and dedication. In the context of a relentlessly bleak news cycle, they are a wholly virtuous expression of national identity, signifying all that is great about Britain. On the other hand, although national treasures are constructed as being 'of the people', by authenticating the underpinning institutional forms of validation, their status transformation contributes to the legitimation and reproduction of status hierarchies, cultural authority and inequality in the UK.